Plant health testing of herbaceous legumes (Mucuna pruriens varieties and Canavalia ensiformis) in the Republic of Benin - Ayodele, M.; Etèka, A.C.; Carsky, R.J. (2000)
Cover crops have been known to harbor some plant pathogens such as fungi, bacteria and viruses which, if not controlled, could infect economic crops. Also the effect of cover crop can be reduced by disease pressure. Therefore, to ensure that pathogens are not disseminated to other countries, CIEPCA established a health certification program for its major cover crops. The program consisted of field inspection and lab testing. The field inspection was done before flowering, which enables roguing of plants infected with viruses and after seed formation, which permitted the examination of the health of the pods. We report on pathogens observed on canavalia ensiformis, Mucuna pruriens var utilis. Mucuna spp.preta, Mucuna spp. Rajada, and Mucuna cochinchinensis. In light of the results of this analysis, it was recommended that seed lots containing colletotrichum lindemuthianum and colletotrichum gloeosporioides should not be disturbed internationally without prior treatment with an efficient fungicide